Nitrogen-doped graphene based triboelectric nanogenerators. (September 2021) - Pace, Giuseppina; Serri, Michele; Castillo, Antonio Esau del Rio; Ansaldo, Alberto; Lauciello, Simone; Prato, Mirko; Pasquale, Lea; Luxa, Jan; Mazánek, Vlastimil; Sofer, Zdenek; Bonaccorso, Francesco
Abstract: Harvesting all sources of available clean energy is an essential strategy to contribute to healing current dependence on non-sustainable energy sources. Recently, triboelectric nanogenerators (TENGs) have gained visibility as new mechanical energy harvester offering a valid alternative to batteries, being particularly suitable for portable devices. Here, the increased capacitance of a few-layer graphene-based electrode is obtained by incorporating nitrogen-doped graphene (N-graphene), enabling a 3-fold enhancement in TENGs' power output. The dependence of TENGs' performance on the electronic properties of different N-graphene types, varying in the doping concentration and in the relative content of N-pyridinic and N-graphitic sites is investigated. These sites have different electron affinities, and synergistically contribute to the variation of the capacitive and resistive properties of N-graphene and consequently, TENG performance. It is demonstrated that the power enhancement of the TENG occurs when the N-graphene, an n-semiconductor, is interfaced between the positive triboelectric material and the electrode, while a deterioration of the electrical performance is observed when it is placed at the interface with the negative triboelectric material. This behavior is explained in terms of the dependence of N-graphene quantum capacitance on the electrode chemical potential which shifts according to the opposite polarization induced at the two electrodes upon triboelectrification. Graphical Abstract: ga1 Highlights: 3-fold power enhancement in TENGs incorporating nitrogen doped-graphene. N-graphenes with different electronic and chemical properties are investigated. N-graphene contributes to the enhanced graphene-electrode capacitance. N-graphene semiconductivity and capacitance are assessed with Raman and impedance spectroscopy. N-pyridinic and N-graphitic sites synergistically contribute to the TENG performance.